Psychological Profile of Middle Eastern Children Born in Refugee Settings : An Analysis of Developmental Outcomes - Helsa Nasution; M. Agung Rahmadi; Luthfiah Mawar; Nurzahara Sihombing (An-Najat, 2025)
This study comprehensively analyzes the psychological and developmental impacts on children born in refugee conditions in the Middle East, utilizing a meta-analytic approach across 47 independent studies (N = 14,892 children) published between 2010 and 2024. Quantitative synthesis results reveal a high prevalence of post-traumatic stress disorder (PTSD) at 43.2% (95% CI: 38.7–47.8%), followed by anxiety at 38.6% (95% CI: 34.2–42.9%), and depression at 35.4% (95% CI: 31.8–39.1%) among refugee children. Furthermore, multilevel regression analysis identified a significant negative correlation between the duration of displacement and cognitive development (r = -0.42, p < .001), delays in language acquisition (r = -0.38, p < .001), as well as deficits in socioemotional functioning (r = -0.45, p < .001). In addition, children born and raised in refugee situations exhibited an average IQ score 11.3 points lower than normative child populations (d = 0.78, p < .001), indicating a long-term and systemic impact. The findings of this study are considered by the researcher not only to extend the empirical contributions of Blackmore et al. (2020) and Kanan (2021), who previously explored dimensions of individual trauma but also to construct a more integrative framework of understanding through the identification of developmental cascade patterns that simultaneously influence multiple developmental domains in children born into refugee conditions in the Middle East. Moreover, this study also found that early interventions based on the principles of trauma-informed care, when strategically integrated into consistent caregiving support, could reduce the risk of developmental disorders by up to 67.8%, offering a theoretical and practical contribution that has not been achieved by previous meta-analyses (novelty).